Regional Perspective of Antimicrobial Stewardship Programs in Latin American Pediatric Emergency Departments - Adriana Yock-Corrales; Gabriela Naranjo-Zuñiga (MDPI AG, 2023)
Antibiotic stewardship (AS) programs have become a priority for health authorities to reduce the number of infections by super-resistant microorganisms. The need for these initiatives to minimize the inadequate use of antimicrobials is essential, and the election of the antibiotic in the emergency department usually impacts the choice of treatment if the patients need hospital admission, becoming an opportunity for antibiotic stewardship. In the pediatric population, broad-spectrum antibiotics are more likely to be overprescribed without any evidence-based management, and most of the publications have focused on the prescription of antibiotics in ambulatory settings. Antibiotic stewardship efforts in pediatric emergency departments in Latin American settings are limited. The lack of literature on AS programs in the pediatric emergency departments in Latin America (LA) limits the information available. The aim of this review was to give a regional perspective on how pediatric emergency departments in LA are working towards antimicrobial stewardship.